Critical philosophy of innovation and the innovator - Pavie, Xavier 1973- (ISTE, Ltd., 2020)
The major innovations which have occurred between the end of the 20th and the beginning of the 21st century represent a fresh challenge to the responsibility of innovators. Innovators have disrupted, and continue to disrupt the world through the growth of technology, DNA sequencing, genetic engineering, the management of large databases, different forms of intrusion into our private lives, etc. It is up to them take full responsibility for their actions, and question what they are accomplishing, why they are accomplishing it, to what end and with what means. Such questionings are those found in a practice conducted by Ancient philosophers: spiritual exercises. These were internal or external discourses, enabling individuals to act, think, to know how to behave and how to master oneself. It is surely toward these practices innovators of today should turn in order to innovate with wisdom.
Includes bibliographical references and indexes. - Online resource; title from PDF title page (John Wiley, viewed August 10, 2020)
Keywords: Technological innovations -- Philosophy; Innovations; Philosophie; Technological innovations; Philosophy